Boundaries for a better life - Kmetec Bitenc, Petra (knjige, 2024)
"Boundaries for better life," is a transformative guide that illuminates the crucial role of personal boundaries in cultivating self-love, respect, and a balanced life. This insightful book offers a deep exploration of how setting healthy boundaries is the key to emotional well-being, stronger relationships, and a profound sense of self-worth. Drawing from real-life scenarios, psychological insights, and practical exercises, it empowers readers to recognize and assert their limits, fostering an environment of mutual respect and personal growth.
Keywords: Kvaliteta življenja; Osebnostni razvoj